Entrance opening of the gateway with an elaborate Dwarashakha - Temples of India Project Team (Jio Institute, 2024)
Main entrance opening of the gateway with an elaborate dwarashakha (architrave or doorjamb). The lintel of this entrance has an image of a Jina and floral motifs on the band above the lintel. Inside the foliated arch design that frames the gateway, there is an inscription which provides the date of the temple's construction. The inscription, on the entrance gate, above the lintel, states that in 1464/1514 CE (VS 1521/71) the Bhandaprasada was built during the reign of Rao Lunkaran. The date is not clear. The inscription is copied here from the inscription in the antarala (antechamber) of the temple.